Human Trafficking in Medieval Europe : Slavery, Sexual Exploitation, and Prostitution - Paolella, Christopher (Social worlds of late antiquity and the early Middle Ages., 2020)
Human trafficking has become a global concern over the last 20 years, but its violence has terrorized and traumatized its victims and survivors for millennia. This study examines the deep history of human trafficking from Late Antiquity to the Early Modern Period. It traces the evolution of trafficking patterns: the growth and decline of trafficking routes, the ever-changing relationships between traffickers and authorities, and it examines the underlying causes that lead to vulnerability and thus to exploitation. As the reader will discover, the conditions that lead to human trafficking in the modern world, such as poverty, attitudes of entitlement, corruption, and violence, have a long and storied past. When we understand that past, we can better anticipate human trafficking's future, and then we are better able to fight it.